Megahertz non-contact luminescence decay time cryothermometry by means of ultrafast PbI2 scintillator - Mykhaylyk, VB; Kraus, H; Bobb, L; Gamernyk, R; Koronski, K (Springer Nature Publishing Group, 2019)
Realtime in situ temperature monitoring in difficult experimental conditions or inaccessible environments is critical for many applications. Non-contact luminescence decay time thermometry is often the method of choice for such applications due to a favorable combination of sensitivity, accuracy and robustness. In this work, we demonstrate the feasibility of an ultrafast PbI2 scintillator for temperature determination, using the time structure of X-ray radiation, produced by a synchrotron. The decay kinetics of the scintillations was measured over the 8–107 K temperature range using monochromatic pulsed X-ray excitation. It is found that lead iodide exhibits a very fast and intense scintillation response due to excitons and donor-acceptor pairs, with the fast decay component varying between 0.08 and 0.5 ns – a feature that can be readily exploited for temperature monitoring. The observed temperature dependence of the decay time is discussed in terms of two possible mechanisms of thermal quenching – transition over activation barrier and phonon-assisted escape. It is concluded that the latter provides a better fit to the experimental results and is consistent with the model of luminescence processes in PbI2. We evaluated the sensitivity and estimated the accuracy of the temperature determination as ca. ±6 K at 107 K, improving to ±1.4 K at 8 K. The results of this study prove the feasibility of temperature monitoring, using ultrafast scintillation of PbI2 excited by X-ray pulses from a synchrotron, thus enabling non-contact in-situ cryothermometry with megahertz sampling rate.